1995
DOI: 10.1148/radiology.196.1.7540310
|View full text |Cite
|
Sign up to set email alerts
|

Malignant liver tumors treated with MR imaging-guided laser-induced thermotherapy: technique and prospective results.

Abstract: MR imaging-guided LITT of liver metastases is a safe and promising therapy for liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
141
0
34

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(181 citation statements)
references
References 0 publications
5
141
0
34
Order By: Relevance
“…The observed cumulative survival curves are entirely comparable with those reported in other series of HCCs treated with percutaneous ablative therapies [6][7][8][9][10][11][12][16][17][18]33 or surgical resection. [13][14][15] Recently, randomized clinical trials showed that RFA is superior to percutaneous chemical injection in terms of both local tumor control and survival.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The observed cumulative survival curves are entirely comparable with those reported in other series of HCCs treated with percutaneous ablative therapies [6][7][8][9][10][11][12][16][17][18]33 or surgical resection. [13][14][15] Recently, randomized clinical trials showed that RFA is superior to percutaneous chemical injection in terms of both local tumor control and survival.…”
Section: Discussionsupporting
confidence: 85%
“…3,4 When surgery is not possible, there are several minimally invasive options for chemical or thermal tumor ablation. [5][6][7][8] One of the most effective is radiofrequency ablation (RFA), 9 which is now considered potentially curative for early-stage HCCs in patients with or without surgical prospects. 3,4,[10][11][12] Local tumor control and survival are the parameters most widely used to assess the efficacy of surgical and nonsurgical treatments for HCC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Laser interstitial thermal ablation therapy has the advantage of being less painful, but the application is usually limited by the relatively small zone of coagulation produced per each probe placement, as similar to MCT. 14,15 Cryoablation therapy is also known to be an effective alternative treatment modality for unresectable liver tumors, but the complication rates have been reported to be relatively high (Ϸ20%). 16,17 The limitations of this study are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…9 According to the American Association for the Study of Liver Diseases (AASLD) practice guidelines, PEI is safe and highly effective for small HCC and should be the standard against which any new therapy is compared. 4 Other alternative nonsurgical treatments include percutaneous acetic acid injection (PAI), 10,11 microwave coagulation therapy (MCT), [12][13][14] laser interstitial thermal ablation therapy, 14,15 cryoablation therapy, 16,17 and radiofrequency ablation (RFA). [18][19][20][21][22][23][24] Among these therapies, RFA is a promising and recently developed thermo-coagulative ablation technique.…”
mentioning
confidence: 99%